Kinetic and equilibrium study of trinitrophenol adsorption onto polyaniline tea waste nanocomposite from aqueous medium - Parmeshwar Lal Meena; Jitendra Kumar Saini; Ajay Kumar Surela; Krishna Poswal (The Holistic Approach to Environment, 2022)
The current study is focused on the synthesis of polyaniline-tea waste nanocomposite (PANI-TWC) material as a competent adsorbent for the effective removal of trinitrophenol (TNP) from aqueous medium. Batch experiments were performed to examine the influence of the various adsorption parameters such as pH, dose of adsorbents, contact time and initial concentration of TNP on the adsorption process. The kinetic data were fitted with pseudo-first and pseudo-second-order models, and the kinetic studies were well explained by the pseudo-second-order kinetic model. Moreover, the adsorption isotherm study for TNP adsorption from aqueous solutions on the PANI-TWC was performed by Langmuir and Freundlich isotherm models. The adsorption equilibrium data were best fitted to the Langmuir isotherm, which indicated that the adsorption surfaces are homogeneous and the adsorption occurred in monolayers.